2022
DOI: 10.1186/s12883-022-02858-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, etiology, and prognosis of hand knob stroke: a case series

Abstract: Background Hand knob stroke is a rare clinical disorder frequently misdiagnosed as peripheral neuropathy. The purpose of this study is to recognize this particular type of stroke by analyzing clinical features, etiology, and prognosis. Methods We enrolled 19 patients with acute hand knob stroke in the Department of Neurology of the Beijing Geriatric Hospital from January 2018 to January 2022, and the clinical and imaging data of the patients during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Wang et al reported that hyperhomocysteinemia was the most common risk factor for hand knob infarction [16], while Orosz et al considered that hypertension was the most common [15]. This last finding was also found by Zhang et al, who observed that hypertension was the most frequent risk factor in patients with hand knob stroke, followed by hyperlipidemia and hyperhomocysteinemia [23]. The table describes the incidence of hand knob stroke in different epidemiological studies (Table 2).…”
Section: Epidemiologymentioning
confidence: 77%
See 1 more Smart Citation
“…Wang et al reported that hyperhomocysteinemia was the most common risk factor for hand knob infarction [16], while Orosz et al considered that hypertension was the most common [15]. This last finding was also found by Zhang et al, who observed that hypertension was the most frequent risk factor in patients with hand knob stroke, followed by hyperlipidemia and hyperhomocysteinemia [23]. The table describes the incidence of hand knob stroke in different epidemiological studies (Table 2).…”
Section: Epidemiologymentioning
confidence: 77%
“…Imaging findings might not be read accurately as the area of the stroke is small, and the pretest probability of stroke would be low. These factors contribute to the low prevalence of reported hand knob strokes, although the actual number of cases may be higher [23]. Additionally, lack of cortical, pyramidal, and cerebellar symptoms results in evaluating physicians favoring a peripheral source.…”
Section: Epidemiologymentioning
confidence: 99%
“…A subsequent case series evaluated the imaging findings of hand knob stroke patients and found that in the majority of ischaemic stroke events, there was variation in the brain lesions, with lesions being present either in the territory of the hand knob or distributed along the path of the MCA. Thirty-one percent of these cases involved medial lesions that resulted in ulnar finger weakness 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Some cases are accompanied by sensory disturbance or cortical symptoms among their previous reports, whereas reports of pure motor isolated finger palsy (PMIFP) caused by localized lesions in the cerebrum without other neurological symptoms except finger palsy are rare [1]. In cases of finger palsy, including PMIFP, PMM, IHP, and IFP, the cerebral localization is typically an infarct in the precentral knob (PK) region characterized by an inverted omega shape on brain images, including computed tomography (CT) or magnetic resonance imaging (MRI) [1,[3][4][5][6]. While the above differential diagnosis is listed for unilateral finger palsy, there is no literature reporting detailed differential points in clinical findings, including neurological findings, because of limited reports of PMIFP by cerebral infarction.…”
Section: Introductionmentioning
confidence: 99%